2019
DOI: 10.2215/cjn.07820618
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Potassium Excretion and Progression of CKD

Abstract: Background and objectives Data on whether low or high urinary potassium excretion is associated with poor kidney outcome have been conflicting. The aim of this study was to clarify the association between urinary potassium excretion and CKD progression.Design, setting, participants, & measurements We investigated the relationship between lower urinary potassium excretion and CKD progression and compared three urinary potassium indices among 1821 patients from the Korean Cohort Study for Outcome in Patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 48 publications
2
52
1
Order By: Relevance
“…Our findings about urinary potassium excretion and BP contrast with those made in general populations and in hypertensive patients, as an inverse association of potassium intake (based on urine measurements) with BP levels has been reported in most of them. 3,6,9,12 In patients with CKD, one study has reported that participants with higher urinary potassium excretion were more likely to have lower systolic BP, 24 whereas others did not find this association, 23,25 as ours did not. Why then would the relation between potassium intake and BP differ in patients with CKD?…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Our findings about urinary potassium excretion and BP contrast with those made in general populations and in hypertensive patients, as an inverse association of potassium intake (based on urine measurements) with BP levels has been reported in most of them. 3,6,9,12 In patients with CKD, one study has reported that participants with higher urinary potassium excretion were more likely to have lower systolic BP, 24 whereas others did not find this association, 23,25 as ours did not. Why then would the relation between potassium intake and BP differ in patients with CKD?…”
Section: Discussioncontrasting
confidence: 45%
“… 18 , 19 In observational studies, high sodium intake based on 24-hour urinary sodium excretion has been associated with increased systolic BP at CKD stages 3–4, 20 , 21 but not at stages 1–2, 22 whereas findings from studies that reported association of potassium intake with BP led to contradictory conclusions. 23 , 24 , 25 As far as the effects of sodium and potassium intake on renal outcomes are concerned, most reports indicate that high sodium intake is associated with more rapid CKD progression, 24 , 26 whereas potassium intake remains a matter of debate. 24 , 27 , 28 …”
mentioning
confidence: 99%
“…Studies using urinary potassium excretion to estimate dietary potassium intake have shown conflicting results regarding the association between urinary potassium excretion and CKD progression. 25 , 26 , 27 , 28 A population-based study in the Netherlands 25 and a Korean study in patients with CKD 26 both demonstrated higher risk for CKD development or progression with low urinary potassium excretion. In contrast, the Chronic Renal Insufficiency Cohort (CRIC) Study in US patients with CKD found that increased urinary potassium excretion was associated with an increased risk for CKD progression, 27 and the Modification of Diet in Renal Disease Study in patients with stages 2-4 CKD showed no association between urinary potassium excretion and kidney failure (defined as initiation of dialysis or kidney transplantation).…”
Section: Influence Of Dietary Potassium Intake On Serum Potassiummentioning
confidence: 99%
“…Multiple observational reports in different severities of CKD explored the association between dietary potassium intake and outcomes that are important to patients (Table 1). 69,71,[82][83][84][85][86][87][88][89] In a majority of them, surrogates of high potassium intake were associated with a lower risk of death or progression of kidney disease. It is unclear if the observed associations are explained by potassium intake or by potassium as a proxy for higher plant consumption [90][91][92] or specific eating patterns, [93][94][95] both of which have been associated with better outcomes in people with and without kidney disease.…”
mentioning
confidence: 99%